(6а(а-х+с)+6х(а+х-с)-6с(а-х-с)
6а в квадрате-6ах+6ас+6ах+6х в квадрате-6сх-6ас+6сх+6с в квадрате
-6ах и +6ах; -6ас и +6ас; -6сх и +6сх -сокращаются, остаётся
6а в квадрате+6х в квадрате+6с в квадрате
всё
дальше решение невозможно
Объяснение:
1) |4-x|<6
__x<4__x=4__x>4__
+ 0 - 4-x
x<4
4-x<6⇒-x<6-4⇒-x<2⇒x>-2 x∈(-2;4]
x>4
-(4-x)<6⇒-4+x<6⇒x<6+4⇒x<10 x∈(4;10)
x∈(-2;10) целых решений : -1,0,1,2,3,4,5,6,7,8,9=11
2) 2|x+3|≤|x-1|⇒2|x+3|-|x-1|≤0
x<-3x=-3-3≤x<1x=1x≥1
- 0 + + x+3
- - 0 + x-1
x<-3
2(-x-3)-(-x+1)≤0⇒-2x-6+x-1≤0⇒-x-7≤0⇒-x≤7⇒x≥-7 x∈[-7;-3)
-3≤x<1
2(x+3)-(-x+1)≤0⇒2x+6+x-1≤0⇒3x≤-5⇒x≤-5/3 x∈[-3;-5/3]
x≥1
2x+6-(x-1)≤0⇒2x+6-x+1≤0⇒x≤-7 x∈∅
x∈[-7;-3)U[-3;-5/3] целых решений: -7,-6,-5,-4,-3,-2=6
6a^2-6xa+6ac+6xa+6x^2-6xc-6ac+6xc+6c^2=6a^2+6x^2+6c^2